Modification of the structural tangent stiffness due to nonlinear configuration-dependent conservative loading - Kurutz, Marta (Computer Assisted Methods in Engineering and Science, 1996)
This paper discusses the effect of deformation-sensitive loading devices. The nature of loading is generally not perfectly dead, namely, it is not perfectly independent of the occurring deflections. However, the Surface tractions or body forces can show some variable characteristics, depending on the actual displacements and causing changes in the classical equilibrium and stability behaviour of the structure. The present analysis concerns the influence of deformation-sensitive loading devices on the structural tangent stiffness. The configuration-dependent loading devices can be characterized by some load- deflection functions, similarly to the material behaviour characterized by stress-strain functions. The effect of loading seems to be similar to that of the material and consequently, the nonlinear loading processes can be handled similarly to the nonlinear materials in the equilibrium analyses of structures. Thus, we can find that in the tangent stiffness of the structure, beside the tangent modulus of the material, the tangent modulus of the load appears. In this paper, the tensorial approach is followed by application to discrete model and the paper is concluded by numerical examples.